The Effect Of Motivation And Work Discipline On Employee Performance At The Ulu Musi Subdistrict Office In Empat Lawang Regency - Novika Trisnawati; Ahmad Soleh; Ida Ayu Made E G (Universitas Dehasen Bengkulu, 2026)
This study aims to determine whether Motivation and Work Discipline affect Employee Performance at the Ulu Musi Sub-District Office in Empat Lawang Regency. The population of this study was all employees at the Ulu Musi Sub-District Office in Empat Lawang Regency, with a sample of 32 people. The sample selection was done using probability sampling with a saturated sample. This study used two independent variables, namely Work Motivation (X1) and Work Discipline (X2), and the dependent variable is Employee Performance (Y). The data collected will be analyzed using data analysis methods, which will first test the classical assumptions before testing the hypothesis. The hypothesis testing in this study uses multiple linear regression with partial testing and simultaneous F testing with a significance level of 0.005%. The results obtained from this study indicate that the variables of Work Motivation and Work Discipline partially influence the Performance of Employees at the Ulu Musi Sub-District Office in Empat Lawang Regency, as seen from the t-test, where the independent variables have a positive effect on performance. Meanwhile, the results of the simultaneous F-test show that Work Motivation and Work Discipline influence the Performance of Employees at the Medan Kota Sub-District Office. Work Motivation and Work Discipline explain 44.0% of the performance variable, while the remaining 56.0% is influenced by other factors outside the variables of Work Motivation and Work Discipline described in this study.